Study of the interaction between the drilling fluid and lake water during the opening of the subglacial Lake Vostok in Antarctica - Danil V. Serbin; Georgii V. Buslaev; Anna Yu. Lavrik; Vyacheslav G. Kadochnikov; Andrei N. Dmitriev (Записки Горного института)
The article presents the laboratory results of formation and breaking of water and organosilicon fluid emulsions, as well as formation and dissociation of nitrogen hydrates under PT conditions close to the conditions at the interface of a glacier and subglacial Lake Vostok using the Gas Hydrate Autoclaves GHA 350 complex. The studied organosilicon fluid was polydimethylsiloxane WACKER AK-10 (in the Russian classification according to GOST 13032-77, PMS-10) with a density of 0.9359 g/cm3 and a kinetic viscosity of 10 mm2/s. We found that a decrease in the emulsion temperature leads to an increase in the time of its breaking, the formation of microemulsions and multiple emulsions of the “oil – in water – in oil” type. This is especially evident at temperatures ≤10 °C. The average emulsion breaking time was 107 s. The minimum emulsion breaking time was observed at a minimum mixer rotation speed of 100 rpm and a maximum temperature of 60 °C, and the maximum emulsion breaking time was observed at a mixer rotation speed of 500 rpm and a temperature of –2.8 °C. We found that nitrogen hydrates were formed at a pressure of 35.0±0.5 MPa and a temperature of ≤ –1 °C.